Inmunohistochemical Identification of Langerhans in Human Cornea - Sedano Gelvet, Eduardo (1997)
We have achieved the identification of Langerhans cells in human cornea epithelium cross sections, fixed in Zenker’s liquid and embedded in paraffin, according to streptavidin-biotin peroxidase immunohistochemical method, in order to demonstrate protein S-100 and muramidase (lisozime) presence in them.Langerhans cells were identified easily from the rest of epithelial cells because they were the only elements protein S-100+ and muramidase+, which were stained light brown and showed rounded outlines with one or two prolongations.Langerhans cells were numerous in the limbic zone and null in the central region.